DAMPAK KETERBUKAAN TEKNOLOGI INFORMASI TERHADAP AKTIFITAS BELAJAR SISWA DI SMP PLUS NURINA BANGSALSARI - Iis Daniyah; Siti Roudlotul Hikamah; Laila Khusnah (FKIP Universitas Islam Jember, 2013)
To open public technology information is appearance one wrong as too characteristic from culture meet modern people special forward in sector IPTEK. Reseat direction this is want there is and do not impact about technology information. About students study special in SMP PLUS NURINA BANGSALSARI, There are also reseat method the to use is : a. The certainly population an sample, b. The gathering method data with to use, Observation method, poll, interview and documenter. For analysis data the gathering Chi Quadrate formula. To be based on analysis to mention so can in conclusion that is : a). There is positive impact very low to open public technology information about study activities in the class. b).There is positive impact very low to open public technology information about study activities in the class.Keywords: Technology, Information